The Politics of Tourism in Asia - Richter, Linda K. (University of Hawai'i Press, 2018)
Tourism, the world's largest industry, has created a variety of complex political problems, particularly in those countries where the primary attraction of tourism is its potential for accelerating development. The political dimensions that have encouraged tourism in the People's Republic of China, the Philippines, Thailand, India, Pakistan, Bangladesh, Sri Lanka, the Maldives, Nepal, and Bhutan are examined in Linda K. Richter's study, which is based on more than 250 interviews with government officials, travel industry representatives, and media officials. Richter concentrates on the reasons for using tourism to advance government policy objectives and on the many ways political and economic problems can frustrate tourism's contribution to national development. All too often, after the expensive infrastructure is developed, luxury good imported, and lavish promotional efforts expended, nations are left disillusions with the economic promise of tourism. Disappointing results are often complicated by a preoccupation with the lure of tourism and an underestimation of the industry's needs and of the political pressures of and on government officials. Encouraging an awareness of the political aspects of tourism, the author advocates greater involvement by social and political scientists in monitoring tourism policy, as well as a restructuring and redesigning of programs in this largest sector of international trade.